Water vapor resistance measured on sweating thermal manikin and Permetest skin model in the vertical orientation - Frederick Fung; Chuansi Gao; Lubos Hes; Vladimir Bajzik (Communications in Development and Assembling of Textile Products)
This paper is a comparison of water vapor resistance (Ret) measured using the Permetest skin model and Tore sweating thermal manikin, i.e. 2D versus 3D methods; and to study the relationship between them. Three materials and five air gap distances were used for the measurement between these two devices, the test conditions in the climatic chambers were set up according to the ISO standard of each measurement method. Results of the correlation coefficient of three materials showed that they all had a strong increasing trend between Permetest and the sweating thermal manikin. From the regression analysis, the P-value of all three materials showed that P< 0.05 and 100% cotton R2=0.83, 50% cotton 50% polyester R2=0.91, 100% polyester R2=0.99. However, Ret resulting values from each device slowed down after 12mm air gap distance.